ISSUES OF ORGANIZING INTERNAL CONTROL OF FULFILLMENT OF TAX OBLIGATIONS OF ENTERPRISES - Djamalov , Hasan; Abdullayev, Abror (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Annotation. The article discusses the economic essence, the need and objectives of organizing corporate control over the fulfillment of tax obligations by business entities, its methodological support, internal and external factors taken into account in the process of developing a corporate standard for this function, the feasibility of using tax management tools in the methodological support of this special type of accounting and analysis, tools have been developed to ensure the completeness, objectivity and reality of the obtained results of one of the effective methods of corporate tax management - internal control.